2023
DOI: 10.1002/adfm.202300425
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Interphase Layer by Flexible Quasi‐Solid Block Polymer Electrolyte to Achieve Highly Stable Lithium Metal Batteries

Abstract: Low safety, unstable interfaces, and high reactivity of liquid electrolytes greatly hinder the development of lithium metal batteries (LMBs). Quasi‐solid‐state electrolytes (QGPEs) with superior mechanical properties and high compatibility can meet the demands of LMBs. Herein, a biodegradable polyacrylonitrile/polylactic acid‐block‐ethylene glycol polymer (PALE) as membrane skeleton for GPEs is designed and systematically investigated by regulating the length and structure of the cross‐linked chain. Benefiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Fourier-transform infrared spectroscopy (FT-IR) and X-ray photoelectron spectroscopy (XPS) were employed for this purpose. The FT-IR analysis (Figure b) revealed shifts in the peaks corresponding to the CO symmetric stretching and CC stretching. Specifically, after the emulsion separation, the peaks shifted from 1632 to 1639 cm –1 and from 1547 to 1536 cm –1 , respectively, compared to fresh CFM–PMDA–TiO 2 . Additionally, the intensities of both peaks decreased, indicating the involvement of PMDA in the reaction process.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Fourier-transform infrared spectroscopy (FT-IR) and X-ray photoelectron spectroscopy (XPS) were employed for this purpose. The FT-IR analysis (Figure b) revealed shifts in the peaks corresponding to the CO symmetric stretching and CC stretching. Specifically, after the emulsion separation, the peaks shifted from 1632 to 1639 cm –1 and from 1547 to 1536 cm –1 , respectively, compared to fresh CFM–PMDA–TiO 2 . Additionally, the intensities of both peaks decreased, indicating the involvement of PMDA in the reaction process.…”
Section: Resultsmentioning
confidence: 96%
“…Furthermore, the XPS analysis (Figure 5c) was used to investigate changes in the surface chemical state of the CFM−PMDA− TiO 2 before and after emulsion separation. The observation of minimal changes in the Ti peak indicated that the structure of TiO 2 remained intact 38 (Figure S14). This change may be attributed to the involvement of titanium in the demulsification process.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It lacks oxygen atoms, and the nitrogen atom in PAN does not strongly interact with lithium ions. Its ionic conductivity can reach 3 mS cm −1 while possessing an electrochemical window exceeding 4.5 V. 159–163 However, due to its low strength and poor mechanical properties, PAN has been used predominantly utilized as a gel polymer electrolyte (GPE) for a long period. 164…”
Section: Nitrile-based Solid Polymer Electrolytesmentioning
confidence: 99%
“…The functional group of the GPE polymer substrate is electronegative and can form a solvated structure of lithium ions, which is conducive to the uniform deposition of lithium ions. Chai et al [124] prepared PALE GPEs using polyacrylonitrile/polylactic acid-block-ethylene glycol polymer (PALE) by adjusting the chain length and the cross-linked segments structure. The groups (-OH, -C-O-C-, -C=O, and -C≡N) on the polymer chain induce the migration of lithium ions along the polymer chain.…”
Section: The Relationship Between Gpes and Seismentioning
confidence: 99%
“…Reproduced from Ref [123]. with permission from Elsevier; (i) the deposition mechanism of Li + ions and a schematic diagram of the Li anode surface in batteries assembled with LE, PAL, and PALE-3-6 GPEs[124]. Reproduced from Ref [124].…”
mentioning
confidence: 99%